Lichen Sclerosus—Presentation, Diagnosis and Management - Kirtschig, Gudula (Dtsch Arztebl Int, 2016)
BACKGROUND: Lichen sclerosus is a chronic inflammatory skin disease. It is thought to be underdiagnosed and undertreated. If it is not treated, lichen sclerosus is associated with a greater degree of scarring and an elevated risk of cancer in the genital area. METHODS: This review is based on pertinent articles published up to October 2015 that were retrieved by a selective search in PubMed, Embase, and the Cochrane Library and on the European S3 guideline for lichen sclerosus. RESULTS: Lichen sclerosus is mainly found in the anogenital area but can also be generalized. Extragenital involvement is reportedly present in 6% to 20% of patients. Neighboring mucous membranes, such as the vaginal or oral mucosa, are not typically affected. The disease is more common in women than in men, and occurs more often in adults than in children. About 10% of patients have other family members with the same condition. Anogenital lichen sclerosus often causes itching and pain. Functional impairment due to fissures and scars can arise over the course of the condition. The treatment of first choice is the local application of high-potency corticosteroids as early as possible (1/A). For boys and men in whom the condition does not remit after steroid treatment, circumcision is indicated (3/D). CONCLUSION: Anogenital itching and clinical features such as erythema, white skin changes (such as hyperkeratosis and sclerosis), and fissures should arouse suspicion of lichen sclerosus. The diagnosis should be confirmed with a skin biopsy, and early, thorough treatment should be initiated. In this way, a mutilating disease course can be averted, and the risk of cancer can be lessened.